2013
DOI: 10.1016/j.bbagen.2013.06.042
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunoproteomics method for identifying in vivo-induced Campylobacter jejuni antigens using pre-adsorbed sera from infected patients

Abstract: This new analysis method may prove to be useful for identifying in vivo-induced antigens within any host infected by bacteria and will contribute to the development of new subunit vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Considering the crucial role of dnaK in antigenic mimicry and GBS, it can be concluded that individuals infected with C. jejuni strains that have sialylated LOS classes and the selected capsular serotypes as well as a high expression pro le of dnaK may be more likely to develop GBS. Furthermore, dnaK gene can be mentioned as an antigen candidate in preventive studies or as a diagnostic marker [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the crucial role of dnaK in antigenic mimicry and GBS, it can be concluded that individuals infected with C. jejuni strains that have sialylated LOS classes and the selected capsular serotypes as well as a high expression pro le of dnaK may be more likely to develop GBS. Furthermore, dnaK gene can be mentioned as an antigen candidate in preventive studies or as a diagnostic marker [10].…”
Section: Discussionmentioning
confidence: 99%
“…Post-infection diseases like GBS with C. jejuni have been proved to be associated with antibodies of human gangliosides. The induction of these autoantibodies is associated with molecular mimicry between human gangliosides and bacterial epitopes present at the surface of the Lipo-Oligosaccharide (LOS) [9] and the antibodies response to diarrhea is different to GBS infected by C. jejuni [10]. In addition to antiganglioside antibodies, Heat Shock Proteins (HSP) family can mediate in the autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is common in regions with extensive animal husbandry. There is a different level of infection of cattle, in some countries the infection reaches 29% [5].…”
Section: Diagnosis Of Cattle Campylobacteriosismentioning
confidence: 99%
“…The in vivo gene expression profiles were evaluated by comparing the level of RNA transcription on DOC and CCDA plates with the expression of virulence genes induced with sodium deoxycholate [10,14]. The total RNA was extracted using TRIzol (TaKaRa, Dalian, China) according to the manufacturer's instructions after a 15 h culture of strain NCTC 11168 on CCDA or DOC plates.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%